Legal vision for international financial institution transactions - المياحي عمار فوزي; احمد ليلى فوزي (Journal of Legal Sciences, 2021)
The increasing restrictions imposed on foreign banks operating in developing countries since the 2007/2007 global financial crisis impede improving growth prospects by limiting the flow of financing resources that are desperately needed by companies and the family sector. Global banks can have important development benefits، but they are not a panacea, and they also carry risks. Policymakers in developing countries are improving by examining how to maximize the benefits of cross-border banking services while keeping their costs down to a minimum. The 2007-2009 crisis and its ensuing decline in economic activity prompted a widespread reassessment of the benefits and costs of international banking and led to the imposition of Restrictions that have impeded the ten years of globalization of financial services and cross-border lending. However, developing countries may need to reconsider the value of global banks as important gates of global credit and accelerate economic growth even as they continue to manage risk. As ambitions continue to increase around the world، and the banking sector develops، there is a crucial question: Will financing be a friend or enemy in the struggle to end poverty?.. Global banks create risks of exporting instability, especially for countries with weak systems and institutions، and must be mitigated. The severity of these risks. But without a competitive banking sector، the poor will not have access to basic financial services، many companies will exit the market، and growth in developing countries will stall. ” Bank financing is essential for a vibrant private sector، especially for nurturing small and medium enterprises. Developing countries can derive the maximum benefits from a stronger banking system while providing protection from risks by improving information sharing across credit records، vigorously enforcing property and contract rights، and ensuring strong supervision of banks. With developed country banks in decline after the crisis، developing country banks have filled the void and expanded across borders، accounting for 60 percent of new banking restrictions since the downturn. The result has been an increase in banking relations between developing countries and the regionalization of international banking operations.